Muslim wife's rights to maintenance: husband's duty to maintain a working wife in Islamic law and the law in Malaysia - Mohd, Azizah; Hj Ibrahim, Badruddin (International Islamic University Malaysia, 2010)
Islamic law imposes a duty on the husband to maintain his wife. This duty arises as soon as the marriage contract is completed. The duty arises as soon as the marriage contract is completed. The duty to maintain her continues until the contract of marriage ends either through death or separation. This paper seeks to examine the provisions of Islamic law on the husband's duty to maintain a working wife. The examination extends to the adequacy of provisions of the law in Malaysia governing maintenance of a Muslim wife. The paper will further analyze the law on the extended duty of the husband to maintain the wife, even though the wife is working and especially earning a good salary of her own.